Constitutively expressed rat mRNA encoding a 70-kilodalton heat-shock-like protein. - O'Malley, K (1985)
A nearly full-length cDNA clone isolated from the rat pheochromocytoma cell line, PC12, revealed extensive nucleotide sequence similarity between the rat cDNA and the Drosophila melanogaster hsp70 gene. The rat recombinant clone encodes a 71,000-dalton protein that is 70% identical with the dipteran hsp70 protein. Remarkably, a truncated segment of this cDNA clone was originally isolated by immunoreactivity with antisera raised to catecholamine-synthesizing enzymes, suggesting that this heat shock protein and these catecholamine enzymes shared antigenic determinants. The rat hsp70-related mRNA is responsible for the production of a constitutive hsp70 protein, because it is present in abundant amounts in various tissues at normal growth temperatures and is only minimally induced by hyperthermia. The rat hsp70-related sequence is part of a multigene family that extends across species to mice and humans.